Kultur In-vitro Anggur Laut (Caulerpa lentilifera) dan Identifikasi Jenis Mikroba yang Berasosiasi - SUNITI, NI WAYAN; SUADA, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
This research aims to find the best condition for the cultivation of fragment of Caulerpa lentilifera, to determine the factors that influence its growth in-vitro, and to identify the types of microbes associated. The study was conducted at the Marine Tech Laboratory and Marine Biology Laboratory of Udayana University. The study begins with the in-vitro culture of C. lentilifera seaweed at the incubator and the tank. The observations of the morphology and the seaweed growth to determine the suitable conditions, the influens of growth factors and microscopic observation to determine the types of microbes were associated. The best results in in-vitro culture in incubator was achieved by provision of 2 ml of PES in 500 ml of sea water, 5000 lux of light intensity, 12 hours irradiation and 100% medium replacement once a week. Best results in-vitro culture in the using net method was achieved by provision of 3500 lux light intensity, 12 hours irradiation and 70% culture replacement once a week. The microbes associated with the C. lentilifera came from the protozoa phylum, flagellate, and cilliata classes.
Keywords: Caulerpa lentilifera, incubator